PATTERNS OF APOLOGETIC UTTERANCES EXPRESSED BY ENGLISH STUDENTS AND NON-ENGLISH STUDENTS - Faiza Hawa; Rahmawati Sukmaningrum (Universitas PGRI Semarang, 2016)
This study aimed at finding out the patterns of apologetic utterance expressed by English department students and non-English department students. The participants of this study were 20 students of English department and 20 students of Biology department students. The data were taken from Discourse Completion Task serving 5 different situations. The responses of the situations were categorized into different patterns of apology offered by Olshtains (1983). The result showed that English students and Biology students have different characteristics in uttering apology. The English students tend to be straight to the point in uttering apology followed by a bit of explanation, while Biology students like to have long apology with more detail explanation. There is no significant difference in the realization of apology speech act uttered by the students. No factor influences the difference in the way they convey apology. Both applies similar various strategies to apologize. Direct apology and Direct Apology followed by Explanation are mostly chosen by the students as the strategies in conveying apology.